Recent advances in metal matrix composites - Lindroos, V.K.; Talvitie, M.J. (Journal of materials processing technology, 1995)
Metal matrix composites is today one of the most actively studied subject in materials science. In this presentation developments in processing, properties and utilisation of light metal matrix composites is reviewed. Additionally, other potential metal matrix composite materials, such as corrosion and wear resistant steel matrix composites are discussed.